What Causes of Customer-Oriented Boundary-Spanning Behaviour? The Role of Personality, Stress, and Creativity - Novita Dwi Lestari; Sinto Sunaryo (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
Customer-Oriented Boundary-Spanning Behaviour (COBSB) reflects employee's behaviour to connect the organization's services with customers. It plays an important role in determining service quality, in which most of the industry depends on the success of this aspect. This study aims to investigate the factors that influence COBSB, considering the role of proactive personality, role stress, and creativity. There were 160 hotel employees in Surakarta, who participated in the survey by using a purposive sampling, while SEM-PLS was conducted to analyse data. The results showed that proactive personality has a positive effect on employee creativity, which in turn influences COBSB in the dimensions of external representation and internal influence. Furthermore, internal influence has a positive effect on service delivery. In addition, internal influence also mediates the effect of employee creativity on service delivery. The findings also showed the negative effect of role stress in the dimensions of role conflict on employee creativity.